2016
DOI: 10.1021/acscatal.6b00421
|View full text |Cite
|
Sign up to set email alerts
|

Implications of CO2 Activation by Frustrated Lewis Pairs in the Catalytic Hydroboration of CO2: A View Using N/Si+ Frustrated Lewis Pairs

Abstract: A series of base-stabilized silylium species were synthesized and their reactivity toward CO 2 explored, yielding the characterization of a novel N/ Si + FLP-CO 2 adduct. These silicon species are active catalysts in the hydroboration of CO 2 to the methoxide level with 9-BBN, catecholborane (catBH), and pinacolborane (pinBH). Both experiments and DFT calculations highlight the role of the FLP-CO 2 adduct in the catalysis. Depending on the nature of the hydroborane reductant, two distinct mechanisms have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 71 publications
1
98
0
Order By: Relevance
“…Diethyl ether, pentane and toluene (Aldrich) were further dried using an LC Technology Solutions SP-105 purification system and stored over 4Å molecular sieves in the glovebox prior to use. The Me 3 Al, Me 3 Ga (Aldrich), and B(C 6 F 5 ) 3 (TCI) reagents were used as-received without further purification.…”
Section: Reagentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Diethyl ether, pentane and toluene (Aldrich) were further dried using an LC Technology Solutions SP-105 purification system and stored over 4Å molecular sieves in the glovebox prior to use. The Me 3 Al, Me 3 Ga (Aldrich), and B(C 6 F 5 ) 3 (TCI) reagents were used as-received without further purification.…”
Section: Reagentsmentioning
confidence: 99%
“…The transformation of the dimethyl Ga complexes 3 and 7 to their bis(pentafluorophenyl) analogs was then targeted and was achieved by heating 3 and 7 in refluxing toluene overnight with an excess of B(C 6 F 5 ) 3 . The concept of Me/C 6 F 5 ligand exchange was first introduced by Klosin et al where it was shown that the reaction of B(C 6 F 5 ) 3 with Me 3 Al produced Al(C 6 F 5 ) 3 and Me 3 B when reacted in non-coordinating solvents [18].…”
Section: Preparation and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations